-36=3r-9

Simple and best practice solution for -36=3r-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=3r-9 equation:


Simplifying
-36 = 3r + -9

Reorder the terms:
-36 = -9 + 3r

Solving
-36 = -9 + 3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3r' to each side of the equation.
-36 + -3r = -9 + 3r + -3r

Combine like terms: 3r + -3r = 0
-36 + -3r = -9 + 0
-36 + -3r = -9

Add '36' to each side of the equation.
-36 + 36 + -3r = -9 + 36

Combine like terms: -36 + 36 = 0
0 + -3r = -9 + 36
-3r = -9 + 36

Combine like terms: -9 + 36 = 27
-3r = 27

Divide each side by '-3'.
r = -9

Simplifying
r = -9

See similar equations:

| 2+3(4x+5)=6 | | (x+2)=3x+5 | | -70-5x=-11x+44 | | -3=4y-6 | | 6x+12-4y+8=6x-15 | | 3x+1-7x=5 | | -5x-62=-12x+22 | | 6x+72-4y+8=6x-15 | | 5(3)-6y=10 | | -10+11x=24+9x | | 2(3)+y=8 | | 5x+3x+4x=30 | | 2(3)+3=8 | | 15x^2-13x+20=0 | | z(z^3+1)=8+z^4 | | 36=4p+9p | | x(2x-3)=(2x+8)(x-5) | | -82-4x=112-11x | | 4(2v+7)+v=25+8v | | -82+7x=-4x+72 | | 3xy+3y=15 | | 6x+10=35-14x | | 1/3x-3=-9 | | ax+bx+cx= | | 8-3x=x-16 | | 1/3x-3=9 | | 3/q=-1/2 | | a/9=99 | | x/8+x/12=5 | | 30x-34x=-3x-4 | | -22+7x=12+5x | | 24+5a+10=-2(1-7a) |

Equations solver categories